Psoriasis Genomics: A Review - Hutasuhut, Magna; Budianti, Windy Keumala; Indriatmi, Wresti; Setyorini, Mirawati (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Psoriasis is a dermatological condition influenced by genetic and epigenetic factors, environmental triggers, as well as immune responses. Genomics refers to the study of individual genes (genomes) and their interactions with environmental influences. In the context of psoriasis genomics, the interplay between genetic predisposition and environmental factors contributes to the manifestation and variations of the disease. With advancements in molecular genotyping technology and genome-wide association studies (GWASs), researchers have identified 50 genetic markers linked to psoriasis. Discussion: Several genetic loci associated with psoriasis have been identified, including PSORS 1-15. The genetics of psoriasis is also linked to its onset, precipitating factors, associated comorbidities, and clinical variations. Advances in psoriasis genomics are leading to more targeted and innovative treatment approaches. The latest therapeutic developments for psoriasis mainly focus on the interleukin-23 (IL-23)/T-helper 17 (Th17) pathways. Conclusion: The development of GWASs provides new knowledge about psoriasis, including its pathogenesis and specific treatments.